2012
DOI: 10.1055/s-0032-1323779
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Work Remains High after Strength Exercise in Elderly

Abstract: Moderate- to high-intensity strength training is recommended for healthy adults. In young subjects, a single session of strength training decreases blood pressure, while heart rate and cardiac work remain elevated afterwards. However, these effects have not been clearly demonstrated in elderly subjects. To investigate this issue, 16 elderly subjects each underwent a Control and an Exercise (3 sets, 8 RM, 9 exercises) session conducted in random order. Haemodynamic variables and heart rate variability were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 28 publications
3
22
0
1
Order By: Relevance
“…These aspects might explain why heart rate remained elevated after the resistance exercise in men. In addition, although men have higher barorefl ex sensitivity to blood pressure decreases than women [ 26 ] , exercise has been shown to decrease barorefl ex sensitivity [ 21 ] , which might explain the inability of heart rate to adequately increase parallel to the decrease in stroke volume and blood pressure in the men. Nevertheless, these are just hypotheses that should be addressed in future researches, since the autonomic control was not evaluated in the present study.…”
mentioning
confidence: 99%
“…These aspects might explain why heart rate remained elevated after the resistance exercise in men. In addition, although men have higher barorefl ex sensitivity to blood pressure decreases than women [ 26 ] , exercise has been shown to decrease barorefl ex sensitivity [ 21 ] , which might explain the inability of heart rate to adequately increase parallel to the decrease in stroke volume and blood pressure in the men. Nevertheless, these are just hypotheses that should be addressed in future researches, since the autonomic control was not evaluated in the present study.…”
mentioning
confidence: 99%
“…Despite evidence regarding the occurrence of post-RE hypotension in older42,43 and hypertensive individuals,44,45 it is important to consider that the magnitude of BP changes in the postexercise period may directly be associated with higher pre-exercise BP levels,46 which was not the case in the present sample. Moreover, as suggested by West et al16 and observed in previous reports,47,48 anticipation of the upcoming stress test may prevent any significant BP reductions after exercise.…”
Section: Discussionmentioning
confidence: 56%
“…14 Another study evaluating HRV among elderly subjects found that cardiac sympathetic modulation and heart rate remained elevated for a long period of time after a single session of strength training. 15 It is important to highlight certain limitations of this preliminary cross-sectional study. First, the effect of resistance training on the sympathetic drive and sympathovagal balance was analysed over a limited period of time.…”
Section: Discussionmentioning
confidence: 92%